First Report of Saprolegnia parasitica from a Marine Species: Gilthead Seabream (Sparus aurata) in Brackish Water Conditions - DINÇTÜRK, Ε.; TANRIKUL, T. T.; BIRINCIOĞLU, S. S. (Journal of the Hellenic Veterinary Medical Society, 2019)
Saprolegniosis is a serious fungal disease that mostly affects freshwater fish species and eggs. It has a cotton wool-like appearance on the body of amphibians, crustaceans and several fish species. Infected gilthead seabream (Sparus aurata) were subjected to clinical, microbiological, parasitological and pathological investigation. On the infected skin samples, grey-white cotton-like patches, erosion of the skin and scale affusion were detected. Lesions covered the whole body of S. aurata in the advanced stages. Bacterial growth and parasitic symptoms were not observed in microbiological examination. Microscopic examination showed hyphaes carrying cysts that were long and branched. In scanning electron microscopy overviews fungal zoospores were observed. In histopathological observations of sections of skin, erosive-ulcerative dermatitis and mycelium of Saprolegnia parasitica were seen in the muscle tissue. Gene sequence-based identification found Saprolegnia parasitica. S. parasitica has not until now been detected in S.aurata. The low salinity of the brackish water is believed to be the predisposing factor of Saprolegniosis in sea bream in this case.